Characteristics of deceased patients with CoVID-19 after the first peak of the epidemic in Fars province, Iran. Issue 1 (1st January 2020) - Emami, Amir; Javanmardi, Fatemeh; Akbari, Ali; Moghadami, Mohsen; Bakhtiari, Hamid; Falahati, Farshad; Hashemi Zadeh Fard Haghighi, Leila; Rezaei, Tahereh
ABSTRACT: Emergence of a new coronavirus causes a serious concern whether this can be stopped at all. The ongoing coronavirus disease created a substantial variation in the fatality rate over the world. The current report brought an explore about the epidemiological characteristics of deceased patients and the fatality rate after the first peak in Fars province which is the fourth most populous and large province in Iran. Of the 3702 confirmed cases with coVID-19, 87 patients passed away and so the fatality rate estimated 2.35. Also, it was derived that male sex, old age and underlying diseases especially diabetes were common characteristics of these victims.